The current role of pentafecta outcomes in open and laparoscopic partial nephrectomy for localized renal tumors - Aly M. Abdel-Karim; Omar A. Bakheet; Gamal Alsagheer; Mostafa AbdelRazek (Український Журнал Нефрології та Діалізу)
Background: Partial nephrectomy (PN) is the standard treatment for managing clinical T1 renal masses. The "trifecta" and "pentafecta" metrics are commonly used to assess the complexity and success of PN procedures. The present study aimed to identify predictive factors associated with the achievement of pentafecta outcomes following PN.